Robust nano-architectured composite thin films for a low-temperature solid oxide fuel cell cathode. Issue 24 (13th April 2016) - Seo, Han Gil; Choi, Yoonseok; Koo, Bonjae; Jang, Ahreum; Jung, WooChul
Abstract : Nano-precipitates of Sm-doped CeO2 were uniformly coated onto porous Pt thin films via cathodic electrochemical deposition. Deposition of only 5 min created an oxide coating that increased the values of the electrode conductance by more than two orders of magnitude and provided outstanding thermal stability even at 600 °C for more than 100 h compared to the bare Pt electrodes. Abstract : Thin-film based, low temperature solid oxide fuel cells (LT-SOFCs) have gained much attention due to their capability to reduce the operating temperature (<450 °C) and the ensuing extended life and reduced cost, compared to conventional SOFCs. While highly porous and continuously connected Pt thin films are viewed as an attractive cathode, they are readily apt to sinter and grow into larger, isolated crystallites upon annealing, leading to severe degradation of the cathode performance over time. Here, we address this issue by fabricating a post-encapsulated composite structure, in which gas-permeable and catalytically active solid electrolytes surround porous Pt electrodes. Nanoporous Pt thin films deposited onto a yttria-stabilized ZrO2 (YSZ) single-crystal substrate are uniformly coated with Sm-doped CeO2 (SDC) via a simple, cost-effective and scalable coating method known as cathodic electrochemical deposition (CELD). Physical characterization of the nanostructured Pt/SDC composite thin films is done using a range of tools, in this case SEM, TEM, XRD and ICP-MS. AC impedance spectroscopy (ACIS) of symmetric cells (cathode|electrolyte|cathode) with SDC coatings reveals that the enhanced Pt–SDC interactions led to exceptionally high ORR activity and outstanding thermal stability. These observations provide new directions for the achievement of a robust and catalytically active LT-SOFC cathode through modification of the metal surface.